Improving Fine Motor Development Through Paper Clay Media in Early Childhood - Nur Khofifah; Endah Tri Wisudaningsih; Debby Adelita Febrianti Purnamasari (Journal of Childhood Development, 2024)
This study is motivated by the results of observations at TP Ar-Rahmah, Rawan Village, Probolinggo Regency District, related to the development of fine motor skills of children who are still not optimally developed. This can be seen from the less than optimal ability of children to move their fingers, eye and hand coordination. The problem in this study is how to improve fine motor skills through playing with paper clay in early childhood at TP Ar-Rahmah, Rawan Village, Probolinggo Regency District. The purpose of this study was to determine the development of fine motor skills through paper clay activities also called pulp paper at TP Ar-Rahmah, Rawan Village, Krejengan District, Probolinggo Regency. The method used in this research is descriptive qualitative with the subject of 10 children, descriptive qualitative research with observation, interview, and documentation assessment techniques. The analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that paper clay activities can help children in improving children's fine motor skills, imagination, and creativity.